Narco‐Cattle Ranching in Political Forests. Issue 4 (26th November 2018) - Devine, Jennifer A.; Wrathall, David; Currit, Nate; Tellman, Beth; Langarica, Yunuen Reygadas
Abstract: In Central America, drug traffickers are deforesting the region's remaining forests and protected areas through a process known as narco‐ganadería, narco‐cattle ranching. Drawing on the case study of Laguna del Tigre National Park, this article argues that narco‐cattle ranching is a key driver of deforestation in Guatemala's Maya Biosphere Reserve. Using ethnographic and remote‐sensing methods, we describe narco‐cattle ranching's money‐laundering practices, its territorial dynamics, and its environmental impacts. We draw on theorisations of "political forests" to explain how drug trafficking organisations transform land use in the reserve, and along the way, remake its ecology, territories and subjects. Our work illustrates that drug policy is inextricably linked to conservation policy in the Americas. More specifically, we argue that community‐based resource management improves forest and protected area residents' abilities to resist drug‐trafficking related land use change by strengthening local governance and land tenure regimes. Resumen: En América Central, los traficantes de drogas están deforestando los bosques y áreas protegidas restantes de la región a través de un proceso localmente conocido como narco‐ganadería. Con base en el estudio de caso del Parque Nacional Laguna del Tigre, este artículo argumenta que no es la agricultura de subsistencia practicada por campesinos sin tierras la que está causando deforestación en la Reserva de la Biósfera Maya de Guatemala, sino la narco‐ganadería. Por medio de métodos etnográficos y de percepción remota, describimos las prácticas de lavado de dinero de la narco‐ganadería, sus dinámicas territoriales y sus impactos ambientales. A partir de teorizaciones de "bosques políticos", explicamos cómo las organizaciones de narcotráfico transforman el uso del suelo en la reserva y, como consecuencia, reconfiguran su ecología, territorios y sujetos. Nuestro trabajo ilustra que la política en materia de drogas está íntimamente relacionada con la política de conservación en las Américas. Más específicamente, sostenemos que el manejo de recursos de manera comunitaria mejora las habilidades de los residentes de áreas protegidas para resistir cambios de uso del suelo relacionados con el tráfico de drogas a través del fortalecimiento de la gobernanza local y de los regímenes de tenencia de la tierra.